1977
DOI: 10.1007/bf03041419
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the antifungal action of potential steroid inhibitors

Abstract: Structure-activity relationships were studied with macrocyclic esters of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

1983
1983
2019
2019

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…23 Subsequent cyclization in the presence of concentrated H 2 SO 4 afforded the condensed quinoxaline 4a, which is a pharmacophoric structure motif with antifungal activity (Scheme 3b). 24 To probe the possible reaction mechanism, some control experiments were carried out (Scheme 4). The radical scavengers TEMPO (2,2,6,6-tetramethylpiperidine, 1-oxy) and DPE (1,1diphenylethylene) resulted in yields of 68% and 55%, respectively (eqn (1)), which indicated that a radical pathway might not be involved in this reaction.…”
mentioning
confidence: 99%
“…23 Subsequent cyclization in the presence of concentrated H 2 SO 4 afforded the condensed quinoxaline 4a, which is a pharmacophoric structure motif with antifungal activity (Scheme 3b). 24 To probe the possible reaction mechanism, some control experiments were carried out (Scheme 4). The radical scavengers TEMPO (2,2,6,6-tetramethylpiperidine, 1-oxy) and DPE (1,1diphenylethylene) resulted in yields of 68% and 55%, respectively (eqn (1)), which indicated that a radical pathway might not be involved in this reaction.…”
mentioning
confidence: 99%